2014 Consensus conference on viscoelastic test–based transfusion guidelines for early trauma resuscitation. Issue 6 (June 2015) - Inaba, Kenji; Rizoli, Sandro; Veigas, Precilla V.; Callum, Jeannie; Davenport, Ross; Hess, John; Maegele, Marc
<x xml:space="preserve">Abstract</x> ABSTRACT There has been an increased interest in the use of viscoelastic testing to guide blood product replacement during the acute resuscitation of the injured patient. Currently, no uniformly accepted guidelines exist for how this technology should be integrated into clinical care. In September 2014, an international multidisciplinary group of leaders in the field of trauma coagulopathy and resuscitation was assembled for a 2-day consensus conference in Philadelphia, Pennsylvania. This panel included trauma surgeons, hematologists, blood bank specialists, anesthesiologists, and the lay public. Nine questions regarding the impact of viscoelastic testing in the early resuscitation of trauma patients were developed before the conference by panel consensus. Early use was defined as baseline viscoelastic test result thresholds obtained within the first minutes of hospital arrival—when conventional laboratory results are not available. The available data for each question were then reviewed in person using standardized presentations by the expert panel. A consensus summary document was then developed and reviewed by the panel in an open forum. Finally, a two-round Delphi poll was administered to the panel of experts regarding viscoelastic thresholds for triggering the initiation of specific treatments including fibrinogen, platelets, plasma, and prothrombin complex concentrates. This report summarizes the findings and recommendations of this consensus conference.